EXPERIENCES WITH SEXUALITY AND AFFECTIVENESS FOR A GROUP OF ADOLESCENTS (Fiep Bulletin - online, 2013)
The themes relating to sexuality and affection are of interest and curiosity among adolescents, despite the increase in sexually transmitted diseases and unplanned pregnancies among them, facts that become public health problems, which negatively affects the quality of life for young people. Therefore, the objective of this study is to know the behavior of adolescents, with regard to their sexuality and affection, to promote creation of contributions to the planning and implementation of effective and efficient actions, depending on the realities experienced by young people. It was used for both, a study of the type of exploratory and descriptive with quantitative approach, made in two schools in the municipal education system in Natal Rio Grande do Norte Brazil, with a sample of 167 adolescents. There was the importance given by adolescents to adolescent pregnancy and accountability for children arising from unplanned pregnancies, particularly among adolescent boys. In this regard, it was noted the diversity of responses among adolescents, which is the challenge of policies and practices directed to this population group.
Keywords: Adolescent Behavior; Pregnancy in Adolescence; Paternity.